2015
DOI: 10.1103/physrevlett.114.133001
|View full text |Cite
|
Sign up to set email alerts
|

Rydberg-Resolved Resonant Inelastic Soft X-Ray Scattering: Dynamics at Core Ionization Thresholds

Abstract: Resonant inelastic x-ray scattering spectra excited in the immediate vicinity of the core-level ionization thresholds of N2 have been recorded. Final states of well-resolved symmetry-selected Rydberg series converging to valence-level ionization thresholds with vibrational excitations are observed. The results are well described by a quasi-two-step model which assumes that the excited electron is unaffected by the radiative decay. This threshold dynamics simplifies the interpretation of resonant inelastic x-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…However, the cross section for such processes is small. For atoms it has been predicted that the probability for Rydberg-spectator shake processes is small [46], and for the N 2 molecule we showed that present state-of-the-art closeto-threshold excited Rydberg RIXS spectra can be described without taking such processes into account [21]. For the analysis of the N 2 spectrum we developed a simple model to account for apparent Rydberg shake process in the decay step [21].…”
Section: E Rydberg Excitationsmentioning
confidence: 92%
See 1 more Smart Citation
“…However, the cross section for such processes is small. For atoms it has been predicted that the probability for Rydberg-spectator shake processes is small [46], and for the N 2 molecule we showed that present state-of-the-art closeto-threshold excited Rydberg RIXS spectra can be described without taking such processes into account [21]. For the analysis of the N 2 spectrum we developed a simple model to account for apparent Rydberg shake process in the decay step [21].…”
Section: E Rydberg Excitationsmentioning
confidence: 92%
“…In the second part of the paper we discuss Rydberg-excited states in terms of a simple two-step model [21], in which the population of Rydberg orbitals in a first excitation step is presumed to be preserved during the second emission step. We interpret possible deviations from this model as due to spectator electron shake processes during the decay step of the scattering process.…”
Section: Introductionmentioning
confidence: 99%
“…In this investigation we include two RIXS decay channels of the |1s À1 O 4a 1 1 i core-excited state; the quasi-elastic scattering back to the ground state |GSi = |1a 2 1 (O1s),2a 2 1 ,1b 2 2 ,3a 2 1 ,1b 2 1 i and the inelastic scattering to the |1b À1 1 4a 1 1 i valence-excited state,…”
Section: Ab Initio Calculationsmentioning
confidence: 99%
“…Vibrationally resolved resonant inelastic X-ray scattering (RIXS) has provided insight into electronic and molecular properties in the gas phase, [1][2][3][4][5][6] in liquids [7][8][9] and in solids. 10,11 Through studies of gas phase O 2 and N 2 , we have gained information on the effect of parity on RIXS selection rules, 6 quantum beats, 3 the potential energy surface (PES) 1 and ionisation thresholds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation